1998
DOI: 10.1038/sj.onc.1201867
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 protein expression interferes with p53-independent apoptotic pathways

Abstract: Loss of normal p53 function was found frequently to interfere with response of cancer cells to conventional anticancer therapies. Since more than half of all human cancers possess p53 mutations, we decided to explore the involvement of mutant p53 in drug induced apoptosis. To further evaluate the relationship between the p53-dependent and p53-independent apoptotic pathways, and to elucidate the function of mutant p53 in modulating these processes, we investigated the role of a p53 temperature-sensitive (ts) mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 49 publications
7
94
0
2
Order By: Relevance
“…This is manifested as increased resistance to etoposide and cisplatin (cis-DDP), two agents commonly employed for cancer chemotherapy. A similar picture has recently been described for murine leukemic M1 cells, where overexpression of the mouse p53vall35 mutant caused increased resistance to apoptosis induced by cisplatin, doxorubicin or g-irradiation (Li et al, 1998). It is conceivable that not all cell types may Figure 4 Transient overexpression of mutant p53 confers increased resistance to cell killing by etoposide.…”
Section: Discussionsupporting
confidence: 59%
“…This is manifested as increased resistance to etoposide and cisplatin (cis-DDP), two agents commonly employed for cancer chemotherapy. A similar picture has recently been described for murine leukemic M1 cells, where overexpression of the mouse p53vall35 mutant caused increased resistance to apoptosis induced by cisplatin, doxorubicin or g-irradiation (Li et al, 1998). It is conceivable that not all cell types may Figure 4 Transient overexpression of mutant p53 confers increased resistance to cell killing by etoposide.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, mutant p53 can regulate gene expression independently of wt p53 (Kim and Deppert 2004), and transfection of mutant p53 into p53-null cell lines enhances their tumorigenic potential (Dittmer et al, 1993) and renders them resistant to apoptosis (Li et al, 1998;Blandino et al, 1999;Matas et al, 2001). In keeping with these observations, p53-mutant transgenic mice are more prone to cancer than p53 knockout mice (Harvey et al, 1995;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 79%
“…These findings implied a coupling between transcriptional activation by mutp53 and its prooncogenic effects, suggesting that a transcriptional regulation mechanism underlies mutp53 oncogenic GOF. Further support for a role of mutp53 in gene regulation was provided by the observation that treating cells with actinomycin D, a potent transcriptional inhibitor, abolished mutp53 GOF as reflected in resistance of L12 cells to DNA damage-induced apoptosis (Li et al, 1998). Many subsequent studies have since then confirmed that a variety of p53 mutants can upregulate the expression of genes involved in various cellular processes implicated in cancerous progression, including growth regulation, metabolism, angiogenesis, drug resistance and genomic instability.…”
Section: Mechanisms Of P53 Gofmentioning
confidence: 99%
“…Particular attention was devoted to the ability of mutp53 to impinge upon apoptotic pathways, primarily as this might be important in the context of efficient killing of tumor cells by chemotherapy and radiotherapy. Here, mutp53 gain of oncogenic function was manifested as the ability of various p53 mutants to interfere with apoptotic cell death upon treatment with various stress inducers, including growth factor deprivation and genotoxic agents such as IR, UV radiation, cisplatin, etoposide, doxorubicin, and a-amanitin (Peled et al, 1996;Li et al, 1998;Blandino et al, 1999;Murphy et al, 2000;Matas et al, 2001;Sigal et al, 2001;Yap et al, 2004). Mutp53 was also reported to protect hepatocytes from a combination of HBV-X protein and TNFa (Lee et al, 2000).…”
Section: Oncogenic Activities Of Mutp53mentioning
confidence: 99%